(untitled) (IITM Journal of Business Studies, 2024)
exchanges together build up the organized segment for securities issued by the public and private companies, central government and the state government. The growth of Mutual Funds is seen to be very slow and to evolve it into modern day Mutual Funds, it took long years. Mutual Funds emerged in Netherlands in 18th century and then and then got to Scotland, Switzerland, and United States in the 19th century. Mutual Fund’s main motive is to provide diversified investment opportunity and deliver it to its investors. The idea of Mutual Funds developed over the years and the investors have received more choices of diversified investment portfolio through it. In today’s world of immense competition and globalization, the success of a company is determined by the market price of its stock. The investors like to invest in those company’s stocks that can give them maximum return or benefits. In early years, when the mutual fund concept was growing, the investors had only a few investment opportunities where they could invest their money. But now the investors have many alternative investment opportunities to invest their savings through different investment channels. One such investment channel is to invest through mutual funds. With the help of both the brokerage houses and the fund managers, who educate the investors and make them aware of mutual find schemes, mutual funds has seen a tremendous growth. Mutual Funds are seen by investors as financial intermediaries who identify investment opportunity, process financial information, formulate investment strategies, invest funds and monitor progress for the investors at very less cost